Drama and digital arts cultures - Cameron, David (Professor); Anderson, Michael, 1969-; Wotzko, Rebecca (Methuen drama engage., 2017)
'Drama and Digital Arts Cultures' is a critical guide to the new forms of playful exploration, co-creativity, and improvised performance made possible by digital networked media. Drawing on examples from games, education, online media, technology-enabled performance and the creative industries, the book uses the elements of applied drama to frame our understanding of digital cultures.